IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT BY USING MIND MAPPING TECHNIQUE AT THE SEVENTH GRADE OF UPTD SMP NEGERI 2 GUNUNGSITOLI UTARA IN 2022/2023 - Adielya Harazaki Harefa; Yasminar Amaerita Telaumbanua; Afore Tahir Harefa; Elwin Piarawan Zebua (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
Improving Students’ Achievement in Writing Procedure Text By Using Mind Mapping Technique at the Seventh Grade of UPTD SMP NEGERI 2 Gunungsitoli Utara in 2022/2023, Adielya Harazaki Harefa, Jl. Yos Sudarso No. 118/E-S Kota Gunungsitoli, Writing is a way of finding out what people know and what people need to learn. Therefore, it is important for students to master writing in their daily life. In learning writing, most of students could not achieve MCC. There was problem faced by the students in studying writing namely: the students were lack of ideas to write procedure text, the students were lack of vocabulary, the students were unable to implement steps in procedure text. Thus, to overcome these problems, the researchers conducted research by using Mind Mapping Technique. The purpose of the research is to improve the students’ achievement in writing by using Mind Mapping Technique. So, to achieve the purpose, the researchers used Classroom Action Research (CAR). This research has been conducted in two cycles, which each cycle consisted of two meetings, and each meeting consisted of four steps, they were planning, action, observation, and reflection. The result of the data in Cycle I showed there were 6 students (24%) got score among 66-75 classified as “Adequate level”; 5 students (20%) got score among 56-65 classified as “Less level”; 9 students (36%) got score among 46-55 classified as “Less level”; 5 students (20%) got score among 36-45 classified as “Less level”. While in Cycle II there were 22 students (88%) got score among 80-90 and 3 students (12%) got score among 66-75. Based on the result, it is concluded that Mind Mapping Technique cani mprove the students’ writing at the seventh grade of SMP Negeri 2 Gunungsitoli Utara.